Positive electrode active material for lithium secondary battery, method for preparing same, and lithium secondary battery comprising same

By forming sulfur-containing and metal-containing coatings on the surface of the positive electrode active material particles of the lithium secondary battery, the problem of chemical instability of the positive electrode active material of the lithium secondary battery is solved, and higher electrochemical characteristics and conductivity are achieved, thereby reducing side reactions and gas generation.

CN119581508APending Publication Date: 2025-03-07SK ON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411238081.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-05
Filing Date
2024-09-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The positive electrode active substances of existing lithium secondary batteries are prone to chemical instability during use, resulting in the accumulation of impurities and unreacted residues on the electrode surface area, which in turn causes gas generation and explosion and other adverse phenomena.

Method used

The positive electrode active material particles containing the core of lithium metal oxide active material are used to form sulfur-containing coatings and metal-containing coatings on the surface of the particles. The coating is formed by heat treatment and semi-wet process to improve electrochemical characteristics and conductivity.

Benefits of technology

It effectively reduces the charge transfer resistance of the battery at a discharge depth of 50%, enhances the lithium ion mobility and conductivity, reduces side reactions and gas generation, and improves the stability and capacity characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581508A_ABST
    Figure CN119581508A_ABST
Patent Text Reader

Abstract

The positive electrode active material for a lithium secondary battery according to the present invention comprises active material particles, the active material particles comprising: an active material core comprising a lithium metal oxide; and a sulfur-containing coating layer and a metal-containing coating layer, the sulfur-containing coating layer and the metal-containing coating layer being formed on the active material core. The charge transfer resistance (Rct) of the active material particles measured at a depth of discharge (DOD) of 50% by individual contact of the measurement probe is 60 [Omega] / cm2 or less. Provided is a lithium secondary battery including a positive electrode active material having both improved conductivity and ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, a preparation method thereof, and a lithium secondary battery comprising the positive electrode active material. More specifically, the present invention relates to a positive electrode active material comprising a lithium metal oxide, a preparation method thereof, and a lithium secondary battery comprising the positive electrode active material. Background Art

[0002] Secondary batteries are batteries that can be repeatedly charged and discharged. With the development of the information communication and display industries, secondary batteries are widely used as a power source for portable electronic communication devices such as camcorders, mobile phones, and notebook computers. In addition, in recent years, battery packs including secondary batteries are being developed and used as a power source for environmentally friendly vehicles such as electric vehicles or hybrid vehicles.

[0003] Examples of secondary batteries include lithium secondary batteries, nickel-cadmium batteries, and nickel-hydrogen batteries. Among them, lithium secondary batteries have high operating voltage and energy density per unit weight, and are advantageous in charging speed and light weight, and therefore are actively being researched and developed.

[0004] A lithium secondary battery may include an electrode assembly including a positive electrode and a negative electrode that are repeatedly stacked. The electrode assembly may further include a separator (separation membrane) disposed between the positive electrode and the negative electrode and an electrolyte that impregnates the electrode assembly.

[0005] Lithium metal oxides can be used as positive electrode active materials for lithium secondary batteries. Examples of the lithium metal oxides include nickel-based lithium metal oxides.

[0006] As the application range of lithium secondary batteries expands, longer life, high capacity and operational stability are required. Therefore, positive electrode active materials that can provide higher capacity are being developed and applied. In addition, in order to realize high-power secondary batteries, positive electrode active materials with high lithium ion mobility and low surface resistance are being developed.

[0007] However, the positive electrode active material having the above characteristics may cause chemical instability. For example, impurities and unreacted residues may exist on the surface of the positive electrode active material particles. In this case, for example, side reactions with the electrolyte may cause gas generation, explosion, and other undesirable effects. Summary of the invention

[0008] 1. Technical issues to be resolved

[0009] A technical problem of the present invention is to provide a positive electrode active material for a lithium secondary battery having improved electrical and electrochemical characteristics.

[0010] A technical problem of the present invention is to provide a method for preparing a positive electrode active material for a lithium secondary battery having improved electrical and electrochemical properties.

[0011] A technical problem of the present invention is to provide a lithium secondary battery having improved electrical and electrochemical characteristics.

[0012] (II) Technical solution

[0013] The positive electrode active material for a lithium secondary battery includes active material particles, the active material particles including: an active material core, the active material core including lithium metal oxide; and a sulfur-containing coating and a metal-containing coating, the sulfur-containing coating and the metal-containing coating formed on the active material core. The charge transfer resistance (R) of the active material particles measured at a depth of discharge (DOD) of 50% by a single contact of a measuring probe ct ) is 60Ω / cm 2 the following.

[0014] In some embodiments, the metal-containing coating may include at least one of tungsten (W), molybdenum (Mo), niobium (Nb), and tantalum (Ta).

[0015] In some embodiments, the sulfur-containing coating may include a lithium-containing sulfur oxide, and the metal-containing coating may include a lithium tungsten oxide.

[0016] In some embodiments, the sulfur content may be 100 ppm to 5000 ppm, and the metal content in the metal-containing coating layer may be 1000 ppm to 9000 ppm, relative to the weight of the active material core.

[0017] In some embodiments, the sulfur content may be 1000 ppm to 5000 ppm, and the metal content in the metal-containing coating layer may be 2000 ppm to 8000 ppm, relative to the weight of the active material core.

[0018] In some embodiments, the active material particles may have a form of secondary particles in which a plurality of primary particles are aggregated, and the sulfur-containing coating layer and the metal-containing coating layer may be formed on outer surfaces of the secondary particles.

[0019] In some embodiments, the sulfur-containing coating layer and the metal-containing coating layer may also be formed between the primary particles inside the secondary particles.

[0020] In some embodiments, the coating amount of the sulfur-containing coating layer and the metal-containing coating layer on the outer surface of the secondary particles may be greater than the coating amount between the primary particles.

[0021] In some embodiments, the R ct Can be 30Ω / cm 2 Up to 60Ω / cm 2 .

[0022] In some embodiments, the active material core may include lithium nickel metal oxide, and the molar fraction of nickel in the lithium nickel metal oxide relative to the total molar number of metals other than lithium and oxygen may be greater than or equal to 0.8.

[0023] A lithium secondary battery includes: a positive electrode including the positive electrode active material for a lithium secondary battery according to the above embodiment; and a negative electrode disposed opposite to the positive electrode.

[0024] In a method for preparing a positive electrode active material for a lithium secondary battery, an active material core particle containing a lithium metal oxide is prepared, a sulfur (S) source and a metal source are mixed with water in an amount of 10% by weight or less relative to the weight of the active material core particle and the active material core particle to form a mixture, and the mixture is heat treated.

[0025] In some embodiments, the heat treatment can be performed without filtering after forming the mixture.

[0026] In some embodiments, the sulfur source may include a sulfur compound containing an ammonium group, and the metal source may include a metal compound containing an ammonium group.

[0027] In some embodiments, when the mixture is formed, the content of water may be 5 wt % or less relative to the weight of the active material core particles.

[0028] (III) Beneficial effects

[0029] According to the above embodiment, the charge transfer resistance (R ct ) is kept within the prescribed range. Therefore, the influence of other components such as adhesives and conductive materials contained in the battery and electrodes and changes in the battery structure caused by charging / discharging can be eliminated, while the electrochemical properties required by the positive electrode active material itself can be achieved.

[0030] A sulfur-containing coating layer and a metal-containing coating layer may be formed on the surface of the single particle. By adjusting the contents of the sulfur-containing coating layer and the metal-containing coating layer to a specified range, the lithium mobility and the conductivity of the positive electrode active material may be improved at the same time.

[0031] In an exemplary embodiment, the coating layer may be formed by a semi-wet process, thereby preventing the deformation of the active material crystal structure caused by wet coating while reducing impurities on the surface of the active material, thereby providing sufficient lithium mobility and conductivity.

[0032] The positive electrode active material for lithium secondary batteries of the present invention and the lithium secondary batteries containing the positive electrode active material can be widely used in electric vehicles, battery charging stations, other green technology fields such as solar power generation and wind power generation using batteries. The positive electrode active material for lithium secondary batteries of the present invention and the lithium secondary batteries containing the positive electrode active material can be used in eco-friendly electric vehicles and hybrid vehicles that prevent climate change by suppressing air pollution and greenhouse gas emissions. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic diagram for explaining a method and apparatus for measuring the charge transfer resistance of a single particle of a positive electrode active material.

[0034] Figure 2 and Figure 3 1 and 2 are respectively a schematic plan view and a schematic cross-sectional view showing a lithium secondary battery according to an exemplary embodiment.

[0035] Figure 4 It is a diagram for explaining a method of applying a charging pulse of each DOD for measuring the charge transfer resistance.

[0036] Figure 5 and Figure 6 The charge transfer resistance (R ct ) and the lithium diffusion coefficient (D Li )’s picture.

[0037] Figure 7 It is a graph showing the charge transfer resistance of each DOD of the example and the comparative example.

[0038] Figure 8 and Fig. 9 These are transmission electron microscope (TEM) images of the internal cross sections of the active material particles of Example 1 and Comparative Example 5, respectively. DETAILED DESCRIPTION

[0039] According to an embodiment of the present invention, there are provided a lithium nickel-based positive electrode active material including a surface coating layer and a lithium secondary battery including the positive electrode active material.

[0040] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings and embodiments. However, these are merely exemplary embodiments, and the present invention is not limited to the specific embodiments illustrated exemplarily.

[0041] <Positive electrode active material for lithium secondary battery>

[0042] The positive electrode active material for a lithium secondary battery according to an embodiment of the present invention (hereinafter, may be simply referred to as the positive electrode active material) may include active material particles containing a lithium metal oxide that allows lithium ions to be reversibly inserted and extracted.

[0043] The positive electrode active material according to an embodiment of the present invention may include a plurality of active material particles. Each individual active material particle may include an active material core containing a lithium metal oxide and a surface coating, and the surface coating includes a sulfur-containing coating and a metal-containing coating formed on the surface of the active material core. The surface coating may cover at least a part of the outer surface of the active material core.

[0044] In some embodiments, in the total weight of the positive electrode active material, the content of the active material particles may be 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, or 90% by weight or more. In one embodiment, the positive electrode active material may substantially consist of the active material particles.

[0045] In one embodiment, the surface coating may cover a part of the surface of the active material core and may be distributed separately from each other in the form of a plurality of islands. In one embodiment, the surface coating may have a continuous single-layer shape and may completely cover the active material core.

[0046] In some embodiments, the sulfur-containing coating may include a lithium-containing sulfur oxide. For example, the sulfur-containing coating may include a compound represented by the following Chemical Formula 1.

[0047] [Chemical Formula 1]

[0048] Li a M b S c O d

[0049] In Chemical Formula 1, 1≤a≤5, 0<b≤4, 1≤c≤4, 1≤d≤8. M may include Na or K.

[0050] For example, the sulfur-containing coating may include Li2SO4, LiNaSO4, LiKSO4, Li2S2O3, etc. In one embodiment, the sulfur-containing coating may include Li2SO4.

[0051] The metal contained in the metal-containing coating may refer to a metal other than lithium or a metal element other than lithium, nickel, cobalt, and manganese. In some embodiments, the metal-containing coating may comprise a compound represented by Chemical Formula 2 below.

[0052] [Chemical Formula 2]

[0053] Li a M b O c

[0054] In Chemical Formula 2, 1 ≤ a ≤ 6, 0 < b ≤ 3, and 1 ≤ c ≤ 9. For example, in Chemical Formula 2, 1 ≤ a ≤ 6, 1 ≤ b ≤ 3, and 2 ≤ c ≤ 9. M may comprise at least one metal element selected from W, Mo, Nb, and Ta.

[0055] In some embodiments, the metal-containing coating may comprise tungsten. In this case, the metal-containing coating may comprise lithium tungsten oxide. In one embodiment, the metal-containing coating may comprise Li2W2O7, Li6W2O9, Li4WO5, Li2WO4, Li2WO3, Li5W2O7, etc.

[0056] The sulfur-containing coating may increase the ionic conductivity of the positive electrode active material. Accordingly, the lithium diffusion characteristics may be enhanced through the positive electrode active material, thereby improving the capacity characteristics of the lithium secondary battery.

[0057] The metal-containing coating may increase the conductivity of the positive electrode active material. Accordingly, the charge transfer characteristics of the positive electrode active material may be enhanced, and the resistance may be reduced. Accordingly, the power characteristics of the lithium secondary battery may be improved.

[0058] As described above, the sulfur-containing coating and the metal-containing coating coexist on the surface of the positive electrode active material, thereby enhancing the ionic conductivity and the conductivity simultaneously.

[0059] For example, the surface coating may act as a barrier against side reactions between the positive electrode active material or the active material particles and the electrolyte. As described above, unreacted lithium sources may dissolve or transfer to the surface of the active material particles and exist as impurities on the surface of the active material particles containing lithium metal oxide. For example, the impurities may comprise Li2CO3 and / or LiOH.

[0060] For example, Li2CO3 may decompose according to Equation 1 below to generate CO2, or may react with HF derived from the electrolyte according to Equation 2 to generate CO2.

[0061] [Equation 1]

[0062] [Formula 2]

[0063] According to an exemplary embodiment, the sulfur component and the metal component may react with the residual lithium to form the sulfur-containing coating and the metal-containing coating, thereby preventing or reducing the generation of Li2CO3 on the surface of the active material particles.

[0064] In some embodiments, a sulfur source (eg, (NH4)2SO4) used to form a sulfur-containing coating may react with residual lithium according to Formulas 3 and 4 below, thereby reducing residual lithium and having a relatively improved performance in suppressing gas generation.

[0065] [Formula 3] (NH4)2SO4 + 2LiOH + H2O → Li2SO4 + 2NH3

[0066] [Formula 4] (NH4)2SO4+ Li2CO3+ 2H2O → Li2SO4+ 2NH3+ CO2

[0067] In some embodiments, the metal source (e.g., (NH4) 10 H2(W2O7)6)) can react with residual lithium according to the following formula 5 and formula 6, thereby reducing the residual lithium.

[0068] [Formula 5] (NH4) 10 H2(W2O7)6·4H2O + 24LiOH → 12Li2WO4+ 22H2O + 10NH3

[0069] [Formula 6] (NH4) 10 H2(W2O7)6·4H2O + 6Li2CO3→ 6Li2W2O7+ 6CO2+ 10H2O + 10NH3

[0070] As described above, the sulfur-containing coating layer having improved ion conductivity and gas suppression characteristics is formed while the metal-containing coating layer is formed, so that the conductivity can be supplemented and the residual lithium can be further reduced.

[0071] In some embodiments, the content of sulfur (S) in the positive electrode active material measured by high frequency inductively coupled plasma (ICP) can be 100 ppm to 5000 ppm. In one embodiment, the content of sulfur measured by ICP can be 500 ppm to 5000 ppm, 1000 ppm to 5000 ppm, 1000 ppm to 4000 ppm or 1000 ppm to 3000 ppm.

[0072] In some embodiments, the content of the metal (W, Mo, Nb and / or Ta) in the positive electrode active material measured by ICP may be 1000ppm to 9000ppm. In one embodiment, the content of the metal measured by ICP may be 1000ppm to 8000ppm, 2000ppm to 8000ppm, 2000ppm to 7000ppm or 3000ppm to 7000ppm.

[0073] Within the above range, the ion conductivity and the electrical conductivity of the positive electrode active material can be enhanced in a balanced manner, and sufficient reduction in residual lithium and gas generation can be achieved.

[0074] In an exemplary embodiment, the active material particle or active material core may have a secondary particle structure formed by a plurality of primary particles being aggregated. For example, the active material particle may have a morphological structure in which 10 or more, 20 or more, 30 or more, 40 or more, 50 or more, 70 or more, or 100 or more primary particles are substantially aggregated in one secondary particle.

[0075] For example, the boundary of the secondary particles can be observed through a cross-sectional image of a scanning electron microscope (SEM), and the cross sections of a plurality of primary particles within the boundary can be observed.

[0076] The sulfur-containing coating layer and the metal-containing coating layer may be formed on the outer surface of the secondary particles. Therefore, the contact resistance between the active material particles may be reduced, and the side reactions and gas generation occurring on the outer surface may be effectively suppressed.

[0077] In some embodiments, the sulfur-containing coating and the metal-containing coating may also partially exist between the primary particles in the inner region of the secondary particles. Thus, the resistance at the interface between the primary particles may be reduced, and the adhesion between the primary particles may be enhanced.

[0078] In some embodiments, the amount of the surface coating present on the outer surface may be greater than the amount between the primary particles. For example, the amount of sulfur and the amount of metal measured on the outer surface may be greater than the amount between the primary particles.

[0079] In an exemplary embodiment, the active material core may include lithium nickel metal oxide. The lithium nickel metal oxide may further include at least one of cobalt (Co), manganese (Mn), and aluminum (Al).

[0080] In some embodiments, the active material core or the lithium nickel metal oxide may include a layered structure or a crystal structure represented by the following Chemical Formula 3.

[0081] [Chemical formula 3]

[0082] Li p Ni q T r O 2+s

[0083] In Chemical Formula 3, 0.9≤p≤1.2, 0.6≤q≤0.99, 0.01≤r≤0.4, and -0.5≤s≤0.1 may be satisfied. As described above, T may include Co, Mn, and / or Al.

[0084] The chemical structure represented by Chemical Formula 3 represents the bonding relationship contained in the layered structure or crystal structure of the positive electrode active material, and does not exclude other additional elements. For example, M may include Co and / or Mn, and Co and Mn may be provided together with Ni as the main active element of the positive electrode active material. Chemical Formula 3 is provided to represent the bonding relationship of the main active elements, and it should be understood that Chemical Formula 3 is a formula including the introduction and substitution of additional elements.

[0085] In one embodiment, in addition to the main active element, an auxiliary element for enhancing the chemical stability of the positive electrode active material or the layered structure / crystal structure may also be included. The auxiliary element may be mixed together into the layered structure / crystal structure to form a bond, and it should be understood that this case is also included in the chemical structure represented by Chemical Formula 3.

[0086] The auxiliary element may include, for example, at least one of Na, Mg, Ca, Y, Ti, Hf, V, Nb, Ta, Cr, Mo, W, Fe, Cu, Ag, Zn, B, Al, Ga, C, Si, Sn, Sr, Ba, Ra, P, and Zr. The auxiliary element may function as an auxiliary active element that contributes to the capacity / power activity of the positive electrode active material together with Co or Mn, such as Al.

[0087] For example, the active material core or the lithium nickel metal oxide may include a layered structure or a crystal structure represented by the following Chemical Formula 3-1.

[0088] [Chemical formula 3-1]

[0089] Li p Ni q M1 r1 M2 r2 O 2+s

[0090] In Chemical Formula 3-1, M1 may include Co, Mn and / or Al. M2 may include the auxiliary elements described above. In Chemical Formula 3-1, 0.9≤p≤1.2, 0.6≤q≤0.99, 0.01≤r1+r2≤0.4, and -0.5≤s≤0.1 may be satisfied.

[0091] The positive electrode active material may further include a coating element or a doping element. For example, an element substantially the same as or similar to the auxiliary element may be used as the coating element or the doping element. For example, one of the above elements or a combination of two or more of the above elements may be used as the coating element or the doping element.

[0092] The coating element or the doping element may be present on the surface of the active material core, or may be permeated through the surface of the active material core and included in the bonding structure represented by the Chemical Formula 3 or Chemical Formula 3-1.

[0093] The active material core may include a nickel-cobalt-manganese (NCM)-based lithium oxide. In this case, an NCM-based lithium oxide having an increased nickel content may be used.

[0094] Ni can be provided as a transition metal related to the power and capacity of a lithium secondary battery. Therefore, as described above, by using a high-content (high-Ni) composition in the positive electrode active material, a high-capacity positive electrode and a high-capacity lithium secondary battery can be provided.

[0095] However, as the Ni content increases, the long-term storage stability and life stability of the positive electrode or secondary battery may be relatively reduced, and the side reaction with the electrolyte may also increase. However, according to an exemplary embodiment, the conductivity can be maintained by including Co, while the life stability and capacity retention characteristics can be improved by Mn.

[0096] In the NCM-based lithium oxide, the content of Ni (e.g., the molar fraction of nickel in the total moles of nickel, cobalt and manganese) may be greater than 0.6, greater than 0.7 or greater than 0.8. In some embodiments, the content of Ni may be 0.8 to 0.95, 0.82 to 0.95, 0.83 to 0.95, 0.84 to 0.95, 0.85 to 0.95 or 0.88 to 0.95.

[0097] In some embodiments, the positive electrode active material may also include a lithium cobalt oxide-based active material, a lithium manganese oxide-based active material, a lithium nickel oxide-based active material, or a lithium iron phosphate (LFP)-based active material (eg, LiFePO 4 ).

[0098] In some embodiments, the positive electrode active material may include, for example, an Mn-rich based active material, a Li rich layered oxide (LLO) / Over Lithiated Oxide (OLO) based active material, or a Co-less based active material having a chemical structure or crystal structure represented by Chemical Formula 4.

[0099] For example, the active material core may include a chemical structure or crystal structure represented by the following Chemical Formula 4.

[0100] [Chemical Formula 4]

[0101] m[Li2MnO3]·(1-m)[Li n JO2]

[0102] In Chemical Formula 4, 0 < m < 1, 0.9 ≤ n ≤ 1.2, and J may include at least one element selected from Mn, Ni, Co, Fe, Cr, V, Cu, Zn, Ti, Al, Mg, and B.

[0103] The charge transfer resistance (R ct ) of each individual active material particle included in the positive electrode active material according to an embodiment of the present invention may be 60 Ω / cm 2 or less. In some embodiments, the charge transfer resistance of each individual active material particle of the positive electrode active material may be less than 60 Ω / cm 2 . In one embodiment, the charge transfer resistance of the positive electrode active material may be 55 Ω / cm 2 or less or 50 Ω / cm 2 or less.

[0104] In one embodiment, the charge transfer resistance of the positive electrode active material may be 30 Ω / cm 2 or more. For example, the charge transfer resistance of the positive electrode active material may be from 30 Ω / cm 2 to 60 Ω / cm 2 , from 30 Ω / cm 2 to 55 Ω / cm 2 or from 30 Ω / cm 2 to 50 Ω / cm 2 .

[0105] Within the above range, sufficient conductivity can be ensured without impairing the ionic conductivity and reducing the gas generation characteristics of the positive electrode active material.

[0106] In an exemplary embodiment, the lithium diffusion coefficient (DLi ) can be 2×10 -9 cm 2 In some embodiments, the lithium diffusion coefficient of each single active material particle of the positive electrode active material may be 2.10×10 -9 cm 2 / second or more or 2.20×10 -9 cm 2 / second or more.

[0107] In one embodiment, the lithium diffusion coefficient of the positive electrode active material may be 5.00×10 -9 cm 2 / second or less. For example, the lithium diffusion coefficient of the positive electrode active material may be 2.10×10 -9 cm 2 / sec to 5.00×10 -9 cm 2 / sec. Therefore, increased conductivity and sufficient ion conductivity can be ensured at the same time.

[0108] As described above, the charge transfer resistance and the lithium diffusion coefficient according to the present invention can be measured from each active material particle.

[0109] Figure 1 This is a schematic diagram for explaining a method and apparatus for measuring the charge transfer resistance of a single particle of a positive electrode active material.

[0110] Reference Figure 1 A measuring probe 60 and a counter electrode 70 are provided in a measuring tank 50 into which an electrolyte is injected. The tip of the measuring probe 60 and the counter electrode 70 may be immersed in the electrolyte.

[0111] For example, the measurement probe 60 may be a microelectrode coated with gold (Au). The counter electrode 70 may use a lithium foil.

[0112] The measuring probe 60 and the counter electrode 70 may be connected to the first current collector 65 and the second current collector 75, respectively, to apply a measuring current or a measuring pulse. The ends of the first current collector 65 and the second current collector 75 may be exposed to the outside of the measuring tank 50, respectively. The first current collector 65 may be fixed to the upper portion or lid of the measuring tank 50 by a sealing material 66, and may be connected to the measuring probe 60.

[0113] The active material particles of the positive electrode active material may be added to the electrolyte. For example, the active material particles may be dispersed on a filter and then immersed in the electrolyte in a water tank.

[0114] Thereafter, the contact between the measurement probe 60 and the single active material particle 90 may be confirmed using the microscope 80 , and then a charge / discharge pulse may be applied to measure the charge transfer resistance and the lithium diffusion coefficient of the single active material particle 90 .

[0115] According to the above embodiment, the charge transfer resistance can be adjusted at the level of a single active material particle rather than at the level of a positive electrode active material layer unit or a positive electrode unit. Therefore, the influence of other components such as a conductive material and a binder other than the active material particles can be excluded, and the resistance characteristics of the active material particles themselves can be measured and utilized.

[0116] In addition, the resistance changes caused by physical variables such as the thickness of the positive electrode and the porosity of the positive electrode active material layer and chemical variables such as the composition of the electrolyte can be eliminated, and the required ion / charge characteristics inherent to the positive electrode active material can be controlled.

[0117] According to an exemplary embodiment, a state of charge (SOC) of 100% may be adjusted to a plurality of depths of discharge (DOD) states, and a charge / discharge pulse may be applied in each DOD state.

[0118] The pulse measurement method can be applied at each DOD state, and the Tafel plot can be drawn according to the applied current to calculate the charge transfer resistance (R ct ) and lithium mobility (lithium diffusion coefficient: D Li ).

[0119] For example, the charge transfer resistance (R ct ) is defined by the following formula (1).

[0120] (1)

[0121] In formula (1), F represents the Faraday constant, R represents the gas constant, T represents the absolute temperature, and i0 represents the exchange current density.

[0122] For example, at DOD 50%, the Tafel curve can be measured according to the size of each charge and discharge pulse, and the value measured from the Tafel curve can be used to calculate i0 in the formula (1) by the following formula (2-1) or formula (2-2). Substituting the calculated i0 into formula (1), the charge transfer resistance can be obtained.

[0123] (2-1)

[0124] (2-2)

[0125] In formula (2-1) and formula (2-2), i represents current density, α represents transfer coefficient (0.5), and η represents overvoltage.

[0126] For example, the lithium diffusion coefficient (D Li ) can be measured using Galvanostatic Intermittent Titration Technique (GITT) analysis and is defined by the following formula (3).

[0127] (3)

[0128] In formula (3), τ represents the constant current pulse application time (duration) (seconds), m B represents the mass of the positive electrode active material (g), V M Indicates the molar volume of the positive electrode active material (cm 3 / mol), M B represents the molar mass of the positive electrode active material (g / mol), and S represents the contact area between the positive electrode active material and the electrolyte (cm 2 ), ΔE s represents the steady-state voltage change (volts), ΔE τ Indicates the voltage change (volts) during the constant current pulse application time to remove the internal resistance voltage drop (IR drop).

[0129] As described above, after measuring or plotting the charge transfer resistance and lithium diffusion coefficient of a single active material particle at multiple DODs, active material particles whose charge transfer resistance and lithium diffusion coefficient at DOD 50% satisfy the above ranges may be used as a positive electrode active material.

[0130] Hereinafter, a method for preparing the positive electrode active material is described. Hereinafter, a method for preparing the positive electrode active material including an active material core having an NCM-based lithium oxide composition is exemplarily described.

[0131] According to an exemplary embodiment, an active material metal source may be prepared. For example, the active material metal source may include a nickel source, a manganese source, and a cobalt source.

[0132] Examples of the nickel source include nickel sulfate (NiSO4), nickel hydroxide (Ni(OH)2), nickel nitrate (Ni(NO3)2), nickel acetate (Ni(CH3CO2)2) and hydrates thereof. Examples of the manganese source include manganese sulfate (MnSO4), manganese hydroxide (Mn(OH)2), manganese nitrate (Mn(NO3)2), manganese acetate (Mn(CH3CO2)2) and hydrates thereof. Examples of the cobalt source include cobalt sulfate (CoSO4), cobalt hydroxide (Co(OH)2), cobalt nitrate (Co(NO3)2), cobalt carbonate (CoCO3) and hydrates thereof.

[0133] In one embodiment, as the nickel source, the manganese source, and the cobalt source, nickel sulfate, manganese sulfate, and cobalt sulfate may be used, respectively.

[0134] In some embodiments, a compound (eg, hydroxide or oxide) containing the above-mentioned coating element or doping element may also be used together.

[0135] According to an exemplary embodiment, the above active material metal sources may be mixed and reacted, for example, by a coprecipitation method to obtain an active material precursor. For example, the active material precursor may be prepared in the form of nickel manganese cobalt hydroxide.

[0136] In order to promote the coprecipitation reaction, a precipitant and / or a chelating agent may be used. The precipitant may include alkaline compounds such as sodium hydroxide (NaOH) and sodium carbonate (Na2CO3). The chelating agent may include, for example, ammonia water, ammonium carbonate, etc.

[0137] The active material precursor and the lithium source may be mixed and reacted by heat treatment to prepare lithium nickel metal oxide particles. For example, the heat treatment temperature may be about 600°C to 850°C.

[0138] The lithium source may include, for example, lithium carbonate (Li2CO3), lithium nitrate (LiNO3), lithium acetate (CH3COOLi), lithium oxide (Li2O), lithium hydroxide (LiOH), etc. These may be used alone or in combination of two or more. In one embodiment, the lithium source may use lithium hydroxide.

[0139] According to some embodiments, impurities (residual lithium) such as LiOH and Li 2 CO 3 may remain on the surface of the active material core particles including lithium metal oxide.

[0140] According to the present invention, the surface coating layer may be formed by a semi-dry method.

[0141] According to an exemplary embodiment, the active material core particles prepared as described above and 10 wt % or less of water relative to the total weight of the active material core particles may be mixed with a sulfur source and a metal source, and then stirred for a prescribed time and heat-treated to form a sulfur-containing coating and a metal-containing coating.

[0142] In some embodiments, the amount of water added may be 8 wt % or less, 7 wt % or less, 6 wt % or less, or 5 wt % or less relative to the total weight of the active material core particles. Considering the coating and stirring efficiency, the amount of water added may be 0.5 wt % or more, 1 wt % or more, 1.5 wt % or more, or 2 wt % or more relative to the total weight of the active material core particles.

[0143] For example, water may be added in an amount of 0.5 to 10 wt %, 1 to 8 wt %, 1 to 7 wt %, 1 to 6 wt %, or 1 to 5 wt % relative to the total weight of the active material core particles.

[0144] In the comparative example, wet coating for forming the surface coating layer may be performed using excess water (e.g., 100% by weight or more relative to the total weight of the active material core particles). In this case, lithium impurities (residual lithium) remaining on the active material core particles may be effectively removed.

[0145] However, excessive water may penetrate into the active material core particles, causing the layered crystal structure to be deformed into a cubic structure or a spinel structure, thereby reducing or changing the capacity characteristics of the positive electrode active material and reducing the life characteristics of the positive electrode active material.

[0146] In addition, the coating source may also penetrate into the active material core particles in large quantities together with excess water, thereby possibly reducing the amount of surface coating. Therefore, sufficient electrical conductivity and ionic conductivity may not be achieved by the coating on the surface of the active material particles.

[0147] In the comparative example, the surface coating may be formed by dry coating without using water (eg, using a ball mill). In this case, an uneven coating may be formed due to aggregation of particles, and residual lithium may not be sufficiently removed.

[0148] However, according to an embodiment of the present invention, a small amount of water within the above range can be used for semi-wet coating. Therefore, the residual lithium can be fully removed, and the amount of the coating material can be concentrated on the surface of the active material particles. In addition, the deformation of the crystal structure of the active material particles of the layered structure can be prevented during the coating process, and the desired capacity characteristics of the positive electrode active material can be maintained.

[0149] In some embodiments, after the active material core particles, water and coating source are mixed, heat treatment can be directly performed without filtering process. Therefore, the loss of coating source and damage to the crystal structure can be suppressed, and the added amount of coating source can be substantially maintained in the surface coating.

[0150] In an exemplary embodiment, as the sulfur source and the metal source, a sulfur compound containing an ammonium group and a metal compound containing an ammonium group can be used respectively. For example, the sulfur source can use ammonium sulfate ((NH4)2SO4), and the metal source can use ammonium paratungstate, ammonium metatungstate, etc.

[0151] Since the sulfur source and the metal source sharing an ammonium group are used, sufficient dispersibility and coating uniformity can be ensured even by a semi-wet coating process using a small amount of water.

[0152] In one embodiment, the heat treatment temperature may be 300°C to 500°C or 350°C to 450°C.

[0153] The amount of the coating source added can be adjusted to meet the above-mentioned range of coating amounts of sulfur and metal.

[0154] <Lithium Secondary Battery>

[0155] Figure 2 and Figure 3 are respectively a schematic plan view and a schematic cross-sectional view showing a lithium secondary battery according to an exemplary embodiment. Figure 3 It is along Figure 2 A cross-sectional view taken along the thickness direction along the line II'.

[0156] Reference Figure 2 and Figure 3 , a lithium secondary battery may include an electrode assembly including a positive electrode 100 and a negative electrode 130. In some embodiments, the electrode assembly may further include a separator 140 between the positive electrode and the negative electrode. The electrode assembly may be housed in a housing 160 together with an electrolyte and impregnated in the electrolyte.

[0157] The positive electrode 100 may include a positive electrode active material layer 110, which is formed by coating the positive electrode active material on the positive electrode collector 105. For example, the positive electrode active material may be mixed and stirred with a binder, a conductive material, a thickener and / or a dispersing material in a solvent to prepare a positive electrode mixture. The positive electrode mixture may be coated on the positive electrode collector 105, dried and rolled to manufacture the positive electrode 100.

[0158] Non-limiting examples of the solvent used in preparing the positive electrode mixture include N-methyl-2-pyrrolidone (NMP), dimethylformamide, dimethylacetamide, N,N-dimethylaminopropylamine, ethylene oxide, tetrahydrofuran, and the like.

[0159] The positive electrode current collector 105 may include, for example, stainless steel, nickel, aluminum, titanium, copper, or an alloy thereof. For example, the positive electrode current collector 105 may include aluminum or an aluminum alloy.

[0160] The binder may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (poly(vinylidene fluoride-co-hexafluoropropylene)), polyacrylonitrile, polymethylmethacrylate, nitrile rubber (NBR), polybutadiene rubber (BR), styrene-butadiene rubber (SBR), etc. In one embodiment, the positive electrode binder may use a PVDF-based binder.

[0161] The conductive material may be added to enhance the conductivity of the positive electrode mixture layer and / or the mobility of lithium ions or electrons. For example, the conductive material may include carbon-based conductive materials such as graphite, carbon black, acetylene black, ketjen black, graphene, carbon nanotubes, vapor-grown carbon fiber (VGCF), carbon fiber, and / or metal-based conductive materials such as perovskite materials such as tin, tin oxide, titanium oxide, LaSrCoO3, and LaSrMnO3.

[0162] As the thickener, for example, carboxymethyl cellulose (CMC) can be used.

[0163] The negative electrode 130 may include a negative electrode collector 125 and a negative electrode active material layer 120 formed by coating a negative electrode active material on the negative electrode collector 125 .

[0164] As non-limiting examples of the negative electrode current collector 125 , copper foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, and the like may be cited.

[0165] The negative electrode active material may be a material that can embed and de-embed lithium ions. For example, the negative electrode active material may include carbon-based materials such as crystalline carbon, amorphous carbon, carbon composites, and carbon fibers; lithium metal; lithium alloys; silicon (Si)-containing materials; tin (Sn)-containing materials, and the like.

[0166] Examples of the amorphous carbon may include hard carbon, soft carbon, coke, mesocarbon microbead (MCMB), mesophase pitch-based carbon fiber (MPCF), and the like.

[0167] Examples of the crystalline carbon may include graphite-based carbons such as natural graphite, artificial graphite, graphitized coke, graphitized MCMB, graphitized MPCF, and the like.

[0168] The lithium metal may include pure lithium metal or lithium metal formed with a protective layer for suppressing dendrite growth and the like. In one embodiment, a layer containing lithium metal deposited or coated on the negative electrode current collector may be used as the negative electrode active material layer. In one embodiment, a lithium thin film layer may be used as the negative electrode active material layer.

[0169] Examples of the elements included in the lithium alloy may include aluminum, zinc, bismuth, cadmium, antimony, silicon, lead, tin, gallium, or indium, and the like.

[0170] The silicon-containing active material may provide further increased capacity characteristics. The silicon-containing active material may include Si, SiO x (0 < x < 2), silicon-carbon composite, metal-doped silicate, or SiO x (0 < x < 2), and the like. The metal may include lithium and / or magnesium.

[0171] For example, the negative electrode active material may be dispersed in a solvent to prepare a negative electrode mixture. The negative electrode mixture may be coated on the negative electrode current collector and then dried and rolled to manufacture a negative electrode. The negative electrode mixture may further include a binder, and may optionally further include a conductive material, a thickener, and the like.

[0172] In some embodiments, the negative electrode may further include a negative electrode active material layer in the form of lithium metal formed by a deposition / coating process.

[0173] Non-limiting examples of the solvent for the negative electrode mixture may include water, pure water, deionized water, distilled water, ethanol, isopropyl alcohol, methanol, acetone, n-propanol, tert-butanol, and the like.

[0174] As the binder, conductive material, and thickener, the above-mentioned substances that can be used in manufacturing the positive electrode may be used.

[0175] In some embodiments, the negative electrode binder may use styrene-butadiene rubber (SBR)-based binders, carboxymethyl cellulose (CMC), polyacrylic acid-based binders, polyethylenedioxythiophene (poly(3,4-ethylenedioxythiophene)) (PEDOT)-based binders, and the like.

[0176] A separator 140 may be disposed between the positive electrode 100 and the negative electrode 130. Through the separator, a short circuit between the positive electrode and the negative electrode may be prevented, and flow of ions may be maintained.

[0177] The separator 140 may include a porous polymer film or a porous non-woven fabric. The porous polymer film may include polyolefin-based polymers such as ethylene polymers, propylene polymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers. The porous non-woven fabric may include high-melting-point glass fibers, polyethylene terephthalate fibers, and the like.

[0178] The separator 140 may further include a ceramic-based material. For example, inorganic particles are coated on the polymer film or dispersed in the polymer film, thereby improving heat resistance.

[0179] The separator 140 may have a single-layer or multi-layer structure including the above-mentioned polymer film and / or non-woven fabric.

[0180] According to an exemplary embodiment, the electrode assembly 150 may be formed by repeatedly disposing the positive electrode 100, the negative electrode 130, and the separator 140. In some embodiments, the electrode assembly 150 may have a jelly roll form formed by winding or z-folding the separator 140.

[0181] In one embodiment, the electrode assembly 150 may have a jelly roll form in which the positive electrode 100, the negative electrode 130, and the separator 140 are wound together. In one embodiment, the electrode assembly 150 may have a jelly roll form in which the cut positive and negative electrodes are arranged in a space formed by repeated zigzag folding of the separator 140.

[0182] In one embodiment, the electrode assembly may be formed by cutting or separating the layers of the positive electrode 100 , the negative electrode 130 , and the separator 140 from each other and repeatedly stacking them.

[0183] For example, the tabs (positive tab and negative tab) may protrude from the positive current collector 105 and the negative current collector 125, respectively, and extend to one side of the case 160. The tabs may be fused to the one side of the case 160 and connected to the electrode leads (positive lead 107 and negative lead 127) extending to the outside of the case 160 or exposed to the outside of the case 160.

[0184] For example, the housing 160 may be a pouch-type housing, a prismatic housing, a cylindrical housing, a coin-type housing, or the like.

[0185] The electrode assembly 150 is accommodated in the case 160 together with an electrolyte, so that a lithium secondary battery may be defined. According to an exemplary embodiment, the electrolyte may use a non-aqueous electrolyte.

[0186] The non-aqueous electrolyte may include a lithium salt and an organic solvent. The lithium salt may be, for example, Li + X - Indicates that, as the anion of the lithium salt (X - ), we can exemplify F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - wait.

[0187] The organic solvent may include an organic compound that has sufficient solubility for the lithium salt and additives and is not reactive in the battery. The organic solvent may include, for example, a carbonate-based solvent, an ester-based solvent, an ether-based solvent, a ketone-based solvent, an alcohol-based solvent, and / or an aprotic solvent.

[0188] The organic solvent may be propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate, diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, vinylene carbonate, methyl acetate (MA), ethyl acetate (EA), n-propyl acetate (n-PA), 1,1-dimethylethyl acetate (DMEA), methyl propionate (MP), ethyl propionate (EP), ethyl fluoroacetate (FEA), ethyl difluoroacetate (DFEA), ethyl trifluoroacetate (TFEA), dibutyl ether, tetraethylene glycol dimethyl ether (TEGDME), diethylene glycol dimethyl ether ( ... ether, DEGDME), dimethoxyethane, tetrahydrofuran (THF), 2-methyltetrahydrofuran, ethyl alcohol, isopropyl alcohol, dimethyl sulfoxide, acetonitrile, diethoxyethane, cyclopentane, γ-butyrolactone and propylene sulfite, etc. These can be used alone or in combination of two or more.

[0189] The non-aqueous electrolyte may further include an additive, such as a cyclic carbonate-based compound, a fluorine-substituted carbonate-based compound, a sultone-based compound, a cyclic sulfate-based compound, a cyclic sulfite-based compound, a phosphate-based compound, a borate-based compound, and the like.

[0190] The cyclic carbonate-based compound may include vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and the like.

[0191] The fluorine-substituted carbonate-based compound may include fluoroethylene carbonate (FEC) and the like.

[0192] The sultone-based compound may include 1,3-propane sultone, 1,3-propene sultone, 1,4-butane sultone, and the like.

[0193] The cyclic sulfate-based compound may include 1,2-ethylene sulfate, 1,2-propylene sulfate, and the like.

[0194] The cyclic sulfite-based compound may include ethylene sulfite, butylene sulfite, and the like.

[0195] The phosphate-based compound may include lithium difluoro bis-oxalato phosphate, lithium difluoro phosphate, and the like.

[0196] The borate-based compound may include lithium bis(oxalate) borate and the like.

[0197] In some embodiments, a solid electrolyte can be used instead of the non-aqueous electrolyte. In this case, the lithium secondary battery can be made into an all-solid-state battery. In addition, a solid electrolyte layer can be provided between the positive electrode 100 and the negative electrode 130 to replace the separator 140.

[0198] The solid electrolyte may include a sulfide-based electrolyte. As non-limiting examples, the sulfide-based electrolyte may include Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiCl-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (m and n are positive numbers, Z is Ge, Zn or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (p and q are positive numbers, M is P, Si, Ge, B, Al, Ga or In), Li 7-x PS 6-x Cl x (0≤x≤2), Li 7-x PS 6-x Br x (0≤x≤2), Li 7-x PS 6-x I x (0≤x≤2), etc. These can be used alone or in combination of two or more.

[0199] In one embodiment, the solid electrolyte may also include an oxide-based amorphous solid electrolyte such as Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3, Li2O-B2O3-ZnO, etc.

[0200] The embodiments of the present invention are further described below with reference to specific experimental examples. The embodiments and comparative examples included in the experimental examples are only used to illustrate the present invention and are not used to limit the claims. Various modifications and variations can be made to the embodiments within the scope of the present invention and the technical concept, which is obvious to those skilled in the art, and it is natural that such modifications and variations belong to the scope of the claims.

[0201] Example 1

[0202] Prepare Li[Ni 0.88 Co 0.09 Mn 0.03 ]Lithium nickel metal oxide particles composed of ]O2 (hereinafter referred to as active material core particles).

[0203] A surface coating is formed on the active material core particles by a semi-wet process. Specifically, (NH4)2SO4 is added as a sulfur source for forming a sulfur-containing coating on the active material core particles, and (NH4) 10 H2(W2O7)6·4H2O was used as a tungsten source for forming a tungsten-containing coating layer (metal-containing coating layer) to satisfy the content described in Table 1, and then 5 wt% of water was added relative to the total weight of the active material core particles.

[0204] Thereafter, after stirring for a predetermined period of time, heat treatment was performed at 400° C. to obtain active material particles having a surface coating layer formed thereon.

[0205] The positive electrode active material, acetylene carbon black (Denka Black) as a conductive material, and PVDF as a binder are mixed in a mass ratio of 94:3:3 to prepare a positive electrode mixture, and then the positive electrode mixture is coated on an aluminum current collector and dried and rolled to manufacture a positive electrode. After the rolling, the electrode density of the positive electrode is adjusted to 3.5 g / cubic centimeter (cc) or more.

[0206] A negative electrode slurry was prepared, which contained 93 wt % of natural graphite as a negative electrode active material, 5 wt % of KS6 as a flake type conductive material, 1 wt % of styrene butadiene rubber (SBR) as a binder, and 1 wt % of carboxymethyl cellulose (CMC) as a thickener. The negative electrode slurry was coated on a copper substrate and dried and rolled to manufacture a negative electrode.

[0207] The positive electrode and negative electrode prepared as described above were respectively notched as specified and stacked, and a separator (polyethylene, 25 μm thick) was provided between the positive electrode and the negative electrode in a zigzag manner to form an electrode assembly.

[0208] The tabs of the positive and negative electrodes are welded separately, the welded electrode assembly is placed in a soft bag, and the three surfaces except the electrolyte injection surface are sealed. The area around the tab is included in the sealing portion. The electrolyte is injected through the electrolyte injection surface, and the electrolyte injection surface is sealed, and then immersed for more than 12 hours.

[0209] A 1 M LiPF6 solution was prepared using a mixed solvent of EC / EMC / DEC (25 / 45 / 30; volume ratio), and then 1 wt% of fluoroethylene carbonate (FEC), 0.5 wt% of 1,3-propane sultone (PS) and 0.3 wt% of 1-propylene-1,3-sultone (Prop-1-ene-1,3-sultone, PRS) were added to prepare the electrolyte.

[0210] Example 2 and Example 3

[0211] A positive electrode active material and a secondary battery were manufactured by the same method as in Example 1, except that the amount of the tungsten source was adjusted so as to obtain the tungsten content described in Table 1.

[0212] Example 4

[0213] A positive electrode active material and a secondary battery were manufactured by the same method as in Example 1, except that a niobium (Nb) source (niobium pentoxide (Nb2O5)) was used instead of a tungsten source to measure the niobium content described in Table 1.

[0214] Example 5

[0215] The positive electrode active material and the secondary battery were manufactured by the same method as in Example 1, except that a molybdenum (Mo) source ((NH4)6Mo7O 24 ) was used to replace the tungsten source to obtain the molybdenum content reported in Table 1.

[0216] Example 6 and Example 7

[0217] A positive electrode active material and a secondary battery were manufactured by the same method as in Example 1, except that the amounts of the sulfur source and the tungsten source were adjusted so as to obtain the sulfur content and the tungsten content described in Table 1.

[0218] Comparative Example 1

[0219] A positive electrode active material and a secondary battery were manufactured by the same method as in Example 1, except that the formation of the surface coating layer was omitted.

[0220] Comparative Example 2

[0221] A positive electrode active material and a secondary battery were manufactured by the same method as in Example 1, except that the formation of the tungsten-containing coating layer was omitted.

[0222] Comparative Examples 3 and 4

[0223] A positive electrode active material and a secondary battery were manufactured by the same method as in Example 1, except that the formation of the sulfur-containing coating layer was omitted and the content of the tungsten source was adjusted to obtain the tungsten (W) content described in Table 1.

[0224] Comparative Example 5

[0225] A positive electrode active material and a secondary battery were manufactured by the same method as in Example 1, except that the surface coating layer was formed by a wet process using 100 wt % of water relative to the weight of the active material core particles, and through filtration, drying and heat treatment.

[0226] Experimental example

[0227] (1) Measurement of sulfur content and coating metal content

[0228] The sulfur content and the coating metal content contained in the positive electrode active materials of the examples and comparative examples were measured using an ICP analysis instrument (Inductively Coupled Plasma-Optical Emission Spectroscopy, Agilent 5800).

[0229] (2) Charge transfer resistance of a single particle (R ct ) and the lithium diffusion coefficient (D Li )

[0230] use Figure 1 The measurement apparatus shown in measures the charge transfer resistance of a single particle of the positive electrode active material.

[0231] Specifically, a single particle was brought into contact with a gold (Au) coated microelectrode having a size of 10 μm using a microscope. Charging and discharging were performed by a galvanostat under the following conditions.

[0232] - Electrolyte: 1 mol dm -3 LiClO4 (1:1=EC:PC, volume ratio)

[0233] - Counter electrode: Li foil

[0234] - Cut off voltage: 4.3-3.0V

[0235] - Initial charge and discharge: CC 0.1C / 0.1C

[0236] In each predetermined DOD state, charge and discharge pulses of currents of 0.2 nA, 0.4 nA, 0.6 nA, 0.8 nA, 1.0 nA, 1.5 nA, 2 nA, and 4 nA were applied, and charge and discharge were repeated.

[0237] like Figure 4 As shown, according to the hybrid pulse power characterization (HPPC) protocol, a charge pulse is applied at each DOD, and a discharge pulse is applied after adjusting the DOD.

[0238] Under each DOD state, the Tafel curve is drawn according to the pulse current. The charge transfer resistance (R ct ) and the lithium diffusion coefficient (D Li), and the charge transfer resistance and lithium diffusion coefficient at DOD 50% were extracted.

[0239] Figure 5 and Figure 6 The charge transfer resistance (R ct ) and the lithium diffusion coefficient (D Li )’s picture.

[0240] Figure 7 It is a graph showing the charge transfer resistance of each DOD of the example and the comparative example.

[0241] (3) Evaluation of gas generation

[0242] The lithium secondary batteries of the embodiments and comparative examples were charged (CC-CV 1.0C 4.20V 0.1C cut-off) to a state of charge (SoC) of 100% and stored in a chamber at 60°C. After 16 weeks of storage, the lithium secondary batteries were taken out of the chamber and the amount of gas generated was measured using gas chromatography. Specifically, in order to measure the total amount of gas generated, a hole was formed in the chamber of a vacuum of a specified volume (V), and the pressure change was measured to calculate the volume of the generated gas, and the evaluation was performed as follows.

[0243] ○: The gas generated is less than 60mL

[0244] △: The gas produced is 60mL to 80mL

[0245] X: The gas produced exceeds 80mL

[0246] (4) Measurement of residual lithium (LiOH, Li2CO3)

[0247] 5.0g of the positive electrode active material prepared by the embodiment and the comparative example and 100g of deionized water were added to a 250mL flask and then stirred at a speed of 100rpm for 10 minutes. The obtained dispersion was filtered with a decompression flask and 100g was taken. The dispersed solution taken was added to an automatic measuring instrument (automatic titrator). With reference to the Warder method, 0.1N HCl was used for automatic titration to measure the values ​​of lithium hydroxide (LiOH) and lithium carbonate (Li2CO3) in the dispersion, and evaluated according to the following benchmarks.

[0248] ○: The content of LiOH and Li2CO3 is less than 6000ppm

[0249] △: The content of LiOH and Li2CO3 is 6000ppm or more and less than 8000ppm

[0250] X: The content of LiOH and Li2CO3 is more than 8000ppm

[0251] (5) Evaluation of resistance increase rate after high temperature cycling (DC-IR measurement)

[0252] At 45°C, charge / discharge twice at 0.5C, CC-CV conditions (SOC 100%), charge again at 0.5CCC-CV conditions, and then discharge at 0.5C until SOC 50%. After that, measure the voltage (first voltage) after standing for 30 minutes. Next, i) discharge at 1C for 10 seconds and then stand for 40 seconds, ii) charge at 0.75C for 10 seconds and then stand for 40 seconds, and then measure the voltage (second voltage). The difference between the first and second voltages is used to measure DC-IR (reference value). At 45°C, after 500 charge and discharge cycles at 1C / 1C, measure DC-IR using the method described above. Evaluate the rate of increase of DC-IR relative to the reference value.

[0253] (6) Capacity retention after high temperature (60°C) storage

[0254] The batteries of the examples and comparative examples were charged (CC-CV 0.5C 4.20V 0.1C cutoff) to a state of charge (SoC) of 100%. After that, after being placed in a chamber at 60°C for 16 weeks, the discharge capacity was measured in a chamber at 25°C, and the discharge capacity retention rate (%) relative to the initial discharge capacity was evaluated.

[0255] The evaluation results are shown in Tables 1 and 2 together.

[0256] [Table 1]

[0257]

[0258] [Table 2]

[0259]

[0260] Refer to Table 1 and Table 2, using a charge transfer resistance of 60Ω / cm 2 The lithium secondary battery of the positive electrode active material of the following single particle example ensures improved lithium transfer characteristics and capacity characteristics. In addition, the generation of residual lithium / gas is reduced, and the resistance is also reduced.

[0261] In Comparative Example 2 where only the sulfur-containing coating layer was formed, the conductivity decreased, and thus the charge transfer resistance increased sharply. As a result, the capacity and resistance characteristics also deteriorated.

[0262] In Comparative Examples 3 and 4 where only the metal-containing coating was formed, residual lithium increased and gas generation due to side reactions increased. In particular, in Comparative Example 4 where there was no sulfur-containing coating and the amount of the metal coating was excessively increased, lithium migration characteristics were excessively reduced.

[0263] Figure 8 and Fig. 9 1 and 2 are transmission electron microscope (TEM) images of the internal cross-sections of the active material particles of Example 1 and Comparative Example 5, respectively. Figure 8 As shown, the layered crystal structure of the positive electrode active material is maintained. However, in Comparative Example 5 in which the surface coating layer is formed by a wet process, as the coating liquid penetrates into the secondary particles, the crystal structure of the active material particles is deformed into a cubic structure and a spinel structure.

Claims

1. A positive electrode active material for a lithium secondary battery, the positive electrode active material for a lithium secondary battery comprising active material particles, the active material particles comprising: an active material core comprising a lithium metal oxide; and a sulfur-containing coating layer and a metal-containing coating layer, wherein the sulfur-containing coating layer and the metal-containing coating layer are formed on the active material core, in, The charge transfer resistance R of the active material particles measured at a depth of discharge (DOD) of 50% by a single contact of a measuring probe ct 60Ω / cm 2 the following.

2. The positive electrode active material for lithium secondary battery according to claim 1, wherein The metal-containing coating includes at least one of tungsten (W), molybdenum (Mo), niobium (Nb), and tantalum (Ta).

3. The positive electrode active material for lithium secondary battery according to claim 1, wherein The sulfur-containing coating layer comprises a sulfur oxide containing lithium, and the metal-containing coating layer comprises a lithium tungsten oxide.

4. The positive electrode active material for lithium secondary battery according to claim 1, wherein The sulfur content is 100 ppm to 5000 ppm, and the metal content in the metal-containing coating layer is 1000 ppm to 9000 ppm, relative to the weight of the active material core.

5. The positive electrode active material for lithium secondary battery according to claim 1, wherein The sulfur content is 1000 ppm to 5000 ppm, and the metal content in the metal-containing coating layer is 2000 ppm to 8000 ppm, relative to the weight of the active material core.

6. The positive electrode active material for lithium secondary battery according to claim 1, wherein The active material particles are in the form of secondary particles in which a plurality of primary particles are aggregated, and the sulfur-containing coating layer and the metal-containing coating layer are formed on outer surfaces of the secondary particles.

7. The positive electrode active material for lithium secondary battery according to claim 6, wherein The sulfur-containing coating layer and the metal-containing coating layer are also formed between the primary particles inside the secondary particles.

8. The positive electrode active material for lithium secondary battery according to claim 7, wherein The coating amount of the sulfur-containing coating layer and the metal-containing coating layer on the outer surface of the secondary particles is greater than the coating amount between the primary particles.

9. The positive electrode active material for lithium secondary battery according to claim 1, wherein The R of the active material particles ct 30Ω / cm 2 Up to 60Ω / cm 2 .

10. The positive electrode active material for lithium secondary battery according to claim 1, wherein The active material core includes lithium nickel metal oxide, and the molar fraction of nickel in the lithium nickel metal oxide relative to the total molar number of metals excluding lithium and oxygen is 0.8 or more.

11. A lithium secondary battery comprising: A positive electrode, the positive electrode comprising the positive electrode active material for a lithium secondary battery according to claim 1; as well as A negative electrode is arranged opposite to the positive electrode.

12. A method for preparing a positive electrode active material for a lithium secondary battery, comprising the following steps: preparing active material core particles comprising lithium metal oxide; mixing a sulfur (S) source and a metal source together with 10 wt % or less of water relative to the weight of the active material core particles and the active material core particles to form a mixture; and The mixture is heat treated.

13. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 12, wherein: After the step of forming the mixture, the heat treatment is performed without filtering.

14. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 12, wherein: The sulfur source comprises a sulfur compound containing an ammonium group, and the metal source comprises a metal compound containing an ammonium group.

15. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 12, wherein: The content of water used in the step of forming the mixture is 5% by weight or less relative to the weight of the active material core particles.